STRUVITE: FORMATION FACTORS AND NUTRIENT RECOVERY FROM WASTEWATER - Nguyen, Thi-Thuy-Trang; Le, Thi-Hoang-Yen; Le, Thi-Hong-Hanh; Bui, Xuan-Thanh (GeoScience Engineering, 2018)
Never human being has to faced such a serious lack of phosphorus and pollutants from human activities. Recovery the nutrients is a new trend which is attached the interests of researchers. Extraction the nutrients, based on struvite crystal from wastewater as nutritious sources have been assessed an urgent solution to solve both of problems below. This review focused on feature characteristics of struvite as a chemical fertilizer for plant, struvite formation process in various wastewaters which are related to physio-chemical conditions and potential of applying this idea into practical. Keywords: Struvite; wastewater; nutrient; recovery https://doi.org/10.2478/gse-2018-0002